2016
DOI: 10.1016/j.radphyschem.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Poly(4-vinyl pyridine) radiografted PVDF track etched membranes as sensors for monitoring trace mercury in water

Abstract: International audiencePoly-4-vinyl pyridine chains were radiografted inside the etched-tracks of PVDF nanoporous membrane. P4VP grafting was found to be localized on the solid PVDF surface. Coating of these PVDF-g-P4VP membranes with a very thin layer of gold results in an ASV electrochemical sensor. Functionalized ion track-etched PVDF-g-P4VP sensors were found very selective and highly sensitive for mercury LOD 5 ng/L. a b s t r a c t By a radiation-induced grafting technique, we have functionalized track-et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…The physical and chemical changes (e.g., chain scission, cross-linking, electric, and dielectric properties) of different polymers have been reviewed depending on LET. 9,10 As a general rule, the bombardment of SHI on polymers creates damage zones along its path and forms a latent track due to its large electronic energy deposition. 11,12 The track diameter depends on the mass and energy of the ions.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical changes (e.g., chain scission, cross-linking, electric, and dielectric properties) of different polymers have been reviewed depending on LET. 9,10 As a general rule, the bombardment of SHI on polymers creates damage zones along its path and forms a latent track due to its large electronic energy deposition. 11,12 The track diameter depends on the mass and energy of the ions.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the same group polymerized poly(4‐vinyl pyridine) (P4VP) in PVDF membrane by radiation‐induced RAFT. [ 119 ] The P4VP functionalization makes the membrane a good sensor for monitoring trace of mercury in water. In this strategy, it is essential to preserve the free radical generated by the track.…”
Section: Track‐etched Nanopore/membrane Fabrication and Functionalizamentioning
confidence: 99%
“…For such purpose, materials based on carbon nanotubes [9], carbon thin film [10], graphene and graphene oxide [11], metal nanoparticles [11,12,13,14], and polymers and membranes [15,16,17] are used as WE. Moreover, the number of publications has been growing on the use of track-etched membranes (TeMs) based on polyvinylidene fluoride (PVDF) as a dual-electrode [18,19,20,21,22,23]. TeMs are thin (5–24 µm), light, and flexible polymeric films with pores with narrow pore-size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Such grafted membranes were transformed into membrane electrode by deposition of gold layer (50 nm) and found to be sensitive to sub-ppb Pb 2+ concentration. Poly(4-vinyl pyridine) (P4VPy) grafted into PVDF was found to be effective in detection of mercury [19,26] with concentrations ng/L after 24 h of absorption and µg/L after 2 h of absorption. Penaeva et al [18] reported the electron-beam-induced graft polymerization of bis[2-(methacryloyloxy)ethyl] phosphate onto PVDF membrane for the detection of uranium (VI) in ppb concentrations from 20 to 100 ppb using square wave cathodic stripping voltammetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation